Banks information policies, financial literacy and household wealth - Margherita Fort; Francesco Manaresi; Serena Trucchi (Institute for the Study of Labor (IZA), 2012)
We investigate the causal effect of financial literacy on financial assets, exploiting banks information policies for identification. In Italy, banks who belong to the PattiChiari consortium have implemented policies aimed at increasing transparency and procedural simplification. These policies may affect individuals' financial literacy without involving any direct cost for clients in terms of time, effort or resources, as we show in the paper. We exploit confidential information on whether individuals have their main bank account in one bank in the PattiChiari consortium to instrument their financial literacy level. We show that these policies have a positive and significant effect on both knowledge of financial instruments and household financial assets. Our results suggest that banks information policies have the potential to be an effective tool to increase individuals' financial literacy and that the relationship between financial literacy and wealth is largely underestimated by standard regression models.
Keywords: D14; G11; 330; financial literacy; wealth; instrumental variables; Bankmarketing; Finanzwissen; Informationsverhalten; Kunden; Privater Haushalt; Vermögen; Italien